Correction: Thermo- and electro-switchable Cs⊂Fe4–Fe4 cubic cage: spin-transition and electrochromism. Issue 73 (7th September 2020) - Glatz, Jana; Chamoreau, Lise-Marie; Flambard, Alexandrine; Meunier, Jean-Francois; Bousseksou, Azzedine; Lescouëzec, Rodrigue
Abstract : Correction for 'Thermo- and electro-switchable Cs⊂Fe4 –Fe4 cubic cage: spin-transition and electrochromism' by Jana Glatz et al., Chem. Commun., 2020, DOI: ; 10.1039/d0cc04279j .